REALISASI PRINSIP KESANTUNAN DALAM TINDAK TUTUR DEKLARASI DI SMA EKASAKTI PADANG - Maulidiani, Nia; Manaf, Ngusman Abdul; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTThe purpose of this study three. First, describe the type of speech act Indonesia language teacher declaration during the teaching and learning process at Ekasakti Padang high school. The second, describes the realization of the principle of politeness in speech acts of  the declaration  of indonesian teachers in the Ekasakti Padang high school. The third, describes the context of the specch acts used by the teacher during the teaching and learning process in Ekasakti Padang high school. Based on the result of the study there are three types of declarations speech act,  namely deciding, prohibiting, and permitting. of  the three types that are most often used by teachers in learning are speech acts decide. Then there are five courtesy principles that the teacher uses during learning, namely the maxim of wisdom, the maxim of generosity, the maxim of praise, the maxim of agreement, and the maxim of conclusions. Of the four maxims which are the most dominant used by the teacher there is a maximal agreement. Next, there are four contexts of speech situations.  Kata Kunci: Prinsip Kesantunan, Tindak Tutur Deklarasi